Back from the Future: Divine Supercomprehension and Middle Knowledge as Ground for Retroactive Ontology - Hollingsworth, Andrew (Neue Zeitschrift für systematische Theologie und Religionsphilosophie, 2019)
In this article, I attempt to solve a problem in Wolfhart Pannenberg's eschatology, which is best understood as a retroactive ontology. Pannenberg argues that the future exerts a retroactive causal and determinative power over the present, though he also claims that said future does not yet concretely exist. The problem can be posed thus: How does a non-concrete future hold retroactive power over the concrete present? I argue that the doctrines of middle knowledge and supercomprehension formulated by the Spanish Jesuit theologian Luis de Molina, provide an adequate solution to this problem while still preserving both the retroactive power of the nonconcrete future as well as genuine human libertarian free choice.